2007
DOI: 10.1073/pnas.0708425104
|View full text |Cite
|
Sign up to set email alerts
|

In vivo multiphoton microscopy of NADH and FAD redox states, fluorescence lifetimes, and cellular morphology in precancerous epithelia

Abstract: Metabolic imaging of the relative amounts of reduced NADH and FAD and the microenvironment of these metabolic electron carriers can be used to noninvasively monitor changes in metabolism, which is one of the hallmarks of carcinogenesis. This study combines cellular redox ratio, NADH and FAD lifetime, and subcellular morphology imaging in three dimensions to identify intrinsic sources of metabolic and structural contrast in vivo at the earliest stages of cancer development. There was a significant (P < 0.05) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

64
901
3
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 916 publications
(1,014 citation statements)
references
References 36 publications
64
901
3
7
Order By: Relevance
“…dents, where cellular autofluorescence lifetimes have been correlated with changes in metabolism associated with cancer, e.g. [12], and in humans, e.g. [13] where studies of skin autofluorescence parameters including lifetime have been correlated with cancer [14,15].…”
Section: Biophotonicsmentioning
confidence: 99%
“…dents, where cellular autofluorescence lifetimes have been correlated with changes in metabolism associated with cancer, e.g. [12], and in humans, e.g. [13] where studies of skin autofluorescence parameters including lifetime have been correlated with cancer [14,15].…”
Section: Biophotonicsmentioning
confidence: 99%
“…In an ex vivo study, MPT/fluorescence lifetime imaging (FLIM) approach has been shown to be useful for demarcating malignant melanoma and BCC [13]. Metabolic imaging of the relative amounts of reduced NADH and FAD using MPT/FLIM was performed to noninvasively monitor cancer progression in another in vivo study [14]. A MPT/confocal laser scanning microscopy system was used to investigate various dermatological diseases such as actinic keratosis and stucco keratosis [51].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, flavin adenine dinucleotide (FAD) fluoresces in its oxidative state. Hence, FAD and NAD(P)H together can provide ratiometric mapping of cellular redox state [14]. However, the majority of these endogenous skin fluorophores require UV excitation.…”
Section: Biophotonicsmentioning
confidence: 99%
“…Each of our cells contain molecules capable of self-fluorescence, especially when activated (excited) by specific light waves. In humans, these fluorescing products are numerous: tryptophan, porphyrins, collagen cross-links, elastin, NADH (nicotinamide adenine dinucleotide), and flavins (FAD, flavin adenine dinucleotide) [36].…”
Section: Disadvantagesmentioning
confidence: 99%